2000
DOI: 10.1046/j.1442-9071.2000.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral choroidal ischaemia and serous retinal detachment in pre‐eclampsia

Abstract: Serious retinal detachment secondary to choroidal ischaemia is an unusual but well-documented cause of visual loss in preeclampsia. Very few cases have been reported in the literature. We report a case of a 26-year-old multigravida with pre-eclampsia who developed bilateral choroidal ischaemia with serious retinal detachments. There was spontaneous resolution of the serous detachment and the choroidal changes in the post-partum period, with residual pigment epithelial changes. Serous retinal detachments in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 7 publications
0
32
1
3
Order By: Relevance
“…17,18 Valluri et al 19 using indocyanine green angiography in pre-eclampsia reported choroidal ischaemia and staining as well as hyperpermeability of choroidal vessels, which suggested severe damage to the choroidal vascular walls. In addition, Sathish et al 18 reported serous retinal detachment secondary to choroidal ischaemia with delayed filling of the choriocapillaries in fluorescein angiograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Valluri et al 19 using indocyanine green angiography in pre-eclampsia reported choroidal ischaemia and staining as well as hyperpermeability of choroidal vessels, which suggested severe damage to the choroidal vascular walls. In addition, Sathish et al 18 reported serous retinal detachment secondary to choroidal ischaemia with delayed filling of the choriocapillaries in fluorescein angiograms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these findings in pre-eclampsia may or may not be associated with blood pressure. 18 Few studies have been performed on the relationship between hypertension and CT. Ahn et al 20 reported an increase in subfoveal CT and the accumulation of subretinal fluid followed by a decrease after blood pressure control in their studies of the retinal and choroidal changes in severe hypertension patients. Iwase et al 21 reported that the relationship between choroidal thickness and systolic blood pressure showed diurnal variation.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of PRES is based in the management of the triggering factor, and the reversibility of the neurological changes mainly depends on the rapid treatment of brain edema. Accelerated hypertension in pre-eclampsia has been commonly associated with retinopathy, optic neuropathy and choroidopathy [20,21]. Our patient developed bilateral choroidal detachment and macular edema, the finding which has not yet been reported in association with PRES or accelerated hypertension.…”
Section: Discussionmentioning
confidence: 52%
“…Retinal detachment [6,18] is reversible and normal vision should return in three weeks or less. There is a direct relation between ischemic infarcts of choriocapillaries and retinal separation.…”
Section: Retinal Detachmentmentioning
confidence: 99%
“…Choriocapillaries infarction was suggested by chronic pigment epithelial change. [18,19] Choroid vascular insuffi ciency is the basis for secondary retinal detachments in PIH. Retinal striae may be the fi rst sign, followed by focal accumulation of sub retinal or sub pigment epithelial exudates at the posterior pole.…”
Section: Retinal Detachmentmentioning
confidence: 99%